Designing Coconut Oil Encapsulated Poly(stearyl methacrylate-co-hydroxylethyl metacrylate) Based Microcapsule for Phase Change Materials - OKTAY, BURCU; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (WILEY-V C H VERLAG GMBH, 2019)
Phase change material (PCM) is an effective energy storage application, which has a relatively low cost. In this study, bio-based PCMs were prepared by using two techniques: encapsulation and UV-curing. Encapsulated-PCM was synthesized by suspension polymerization with stearyl methacrylate (SMA) and hydroxyethyl methacrylate (HEMA). In encapsulation process, the microcapsules were prepared from poly(stearyl methacrylate-co-hydroxyethyl methacrylate) shell and coconut oil (CO) core. UV-cured form stable PCM was also prepared by radical addition polymerization of stearyl methacrylate, hydroxyethyl methacrylate and coconut oil. In UV-curing process as in the second process, coconut oil was trapped within the polymeric network without covalent bonding. Thermal storage feature of encapsulated-PCM and UV-cured form stable PCM was investigated. The melting enthalpy of encapsulated-PCM is 119J/g, which is higher than both the melting enthalpy of pure coconut oil (106J/g) and UV-cured form stable PCM (47J/g). Moreover, thermal degradation results of PCMs show that the maximum thermal decomposition temperature of encapsulated-PCM increased compared with UV-cured from stable PCM.
Keywords: Core-shell; coconut oil; encapsulation; phase change materials; UV-cured PCM; THERMAL-ENERGY STORAGE; N-OCTADECANE; COMPOSITES; STABILITY